"دراسة جدوى تسويقية لإنشاء وكالة سياحة وأسفار -دراسة حالة- وكالة لوس الوادي- " - مروة, ناصري (جامعة الوادي - University of Eloued, 2023)
"من خلال ما تقدم من عرض وتحليل نستنتج ما يأتي: 1. إن حجم الاستثمارات الموجهة الى القطاع السياحي هي من أكبر قطاع بعد السكن والصناعة من حيث رأس المال المستثمر، وهذا يشير الى أهمية السياحة في الجزائر. 2. ضعف اهتمام الجهات الحكومية المختصة بالمجال السياحي والفندقي فيما يتعلق بأعداد دراسات الجدوى الاقتصادية لإنجاح المشاريع الاستثمارية، وهذا يعود الى غياب التنسيق بين الهيئات الحكومية والمؤسسات مثل : الوكالات السياحية والفنادق بهذا الصدد. 3. إن ضعف الوعي السياحي والفندقي للعاملين في الوكالات السياحية من شأنه أن يقلل من اهتمام المستثمرين بشأن اعداد دراسات الجدوى الاقتصادية في هذا المجال. 4. قيام قليلي الخبرة بإعداد دراسات الجدوى الاقتصادية لمشاريع السياحة دون مراعاة طبيعة وموقع وأهمية المشروع السياحي. 5. أن دراسة الجدوى في الوكالة المختارة تنقصها بعض المؤشرات والجداول والتوقعات المهمة للمشاريع الخدمية، مثل القوى العاملة المتخصصة في تقديم الخدمات السياحية وخدمات السفر الخارجية والطعام والشراب والنظافة والديكور والملحقات الصحية والرياضية. " "Through the above presentation and analysis, we conclude the following: 1. The volume of investments directed to the tourism sector is one of the largest sectors after housing and industry in terms of invested capital, and this indicates the importance of tourism in Algeria. 2. The weak interest of the government agencies concerned with the field of tourism and hotels with regard to the preparation of economic feasibility studies for the success of investment projects, and this is due to the lack of coordination between government agencies and institutions such as: tourist agencies and hotels in this regard. 3. The lack of awareness of tourism and hotel workers in tourism agencies would reduce the interest of investors regarding the preparation of economic feasibility studies in this field. 4. Those with little experience preparing economic feasibility studies for tourism projects without taking into account the nature, location and importance of the tourism project. 5. The feasibility study in the selected agency lacks some important indicators, schedules, and expectations for service projects, such as manpower specialized in providing tourism services, foreign travel services, food and drink, hygiene, decoration, and health and sports accessories."
Keywords: دراسة جدوى، تسويقية ، وكالة سياحة ،أسفار